2013
DOI: 10.1007/s00059-013-3914-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of epicardial fat thickness with TIMI risk score in NSTEMI/USAP patients

Abstract: In conclusion, EAT thickness is independently associated with TIMI risk score and may be an emerging risk factor for adverse events in NSTEMI/USAP patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…[38][39][40][41][42][43][44][45] Table 1 presents a summary of the included manuscripts. All systematized manuscripts contain a concise and clear portrayal of the inclusion and exclusion criteria and the method for assessing EAT, either through cardiac CT or TTE (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[38][39][40][41][42][43][44][45] Table 1 presents a summary of the included manuscripts. All systematized manuscripts contain a concise and clear portrayal of the inclusion and exclusion criteria and the method for assessing EAT, either through cardiac CT or TTE (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…38,[43][44][45] One study 43 found a significant association between EAT and GRACE scores (p <0.001), though this was not corroborated by other studies. 38 The angiographic SYNTAX score for coronary lesion severity and the clinical TIMI risk score for adverse coronary events were also found to be significantly linked with EAT.…”
Section: Eat and Acs Risk Scoresmentioning
confidence: 86%
See 2 more Smart Citations
“…Epicardial adipose tissue correlated with the degree of coronary atheromatosis, suggesting that its excessive accumulation might contribute to the development of acute coronary syndrome and coronary total occlusions [52]. In another study, EAT thickness was independently associated with the Thrombolysis in Myocardial Infarction (TIMI) risk score in patients with non-ST-elevation myocardial infarction (NSTEMI) and unstable angina pectoris [53]. In patients with the metabolic syndrome, increased EAT was associated with impaired coronary flow reserve [54].…”
Section: Epicardial Adipose Tissue In the Pathomechanism Of Atherosclmentioning
confidence: 99%